2018
DOI: 10.1016/j.cognition.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Learning and transfer of working memory gating policies

Abstract: knowledge about the tasks we encounter enables us to rapidly and flexibly adapt to novel task contexts. Previous research has focused primarily on abstract rules that leverage shared structure in stimulus-response (S-R) mappings as the basis of such task knowledge. Here we provide evidence that working memory (WM) gating policies – a type of control policy required for internal control of WM during a task – constitute a form of abstract task knowledge that can be transferred across contexts. In two experiments… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 42 publications
5
40
0
Order By: Relevance
“…Prior studies have reported similar RT dynamics as evidence of task automatization (Mohr et al, 2016). Our results indicate that this process should be generalized beyond S-R learning to control policy implementation (Bhandari and Badre, 2018). As such, novel S-R rules are not necessary to trigger adaptive processes indexed by early-trial RT dynamics.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Prior studies have reported similar RT dynamics as evidence of task automatization (Mohr et al, 2016). Our results indicate that this process should be generalized beyond S-R learning to control policy implementation (Bhandari and Badre, 2018). As such, novel S-R rules are not necessary to trigger adaptive processes indexed by early-trial RT dynamics.…”
Section: Discussionsupporting
confidence: 70%
“…As such, novel S-R rules are not necessary to trigger adaptive processes indexed by early-trial RT dynamics. Rather, S-R rule implementation is a special case of control policy implementation (Bhandari and Badre, 2018) i.e., task model assembly, (Duncan et al, 2008;Bhandari and Duncan, 2014) or control-context learning, (Chiu and Egner, 2019), required when task dynamics change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations